2007
DOI: 10.1021/es070567g
|View full text |Cite
|
Sign up to set email alerts
|

Uranium Biomineralization as a Result of Bacterial Phosphatase Activity:  Insights from Bacterial Isolates from a Contaminated Subsurface

Abstract: Uranium contamination is an environmental concern at the Department of Energy's Field Research Center in Oak Ridge, Tennessee. In this study, we investigated whether phosphate biomineralization, or the aerobic precipitation of U(VI)-phosphate phases facilitated by the enzymatic activities of microorganisms, offers an alternative to the more extensively studied anaerobic U(VI) bioreduction. Three heterotrophic bacteria isolated from FRC soils were studied for their ability to grow and liberate phosphate in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(97 citation statements)
references
References 40 publications
(52 reference statements)
7
87
1
Order By: Relevance
“…Both field (Ferris et al, 1987;Konhauser et al, 1993;Bonny and Jones, 2003;Fortin and Langley, 2005;Demergasso et al, 2007) and laboratory (Macaskie et al, 2000;Warren et al, 2001;Rivadeneyra et al, 2006) studies have examined mineral formation in super-saturated systems and have found a close spatial association between bacterial cells and a range of extracellular precipitated mineral phases. Despite the increasing number of studies to claim the importance of passive cell wall biomineralization (Lowenstam and Weiner, 1989;Châtellier et al, 2001;Ben Chekroun et al, 2004;Beazley et al, 2007;Dupraz et al, 2009), the nature of the evidence to date is equivocal. A range of studies have documented associations between bacterial cells and mineral precipitates (Konhauser, 1997(Konhauser, , 1998Arp et al, 1998;Douglas and Beveridge, 1998;Warren et al, 2001;Perez-Gonzalez et al, 2010), but a spatial association in and of itself does not prove a role of the cell wall in the precipitation reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both field (Ferris et al, 1987;Konhauser et al, 1993;Bonny and Jones, 2003;Fortin and Langley, 2005;Demergasso et al, 2007) and laboratory (Macaskie et al, 2000;Warren et al, 2001;Rivadeneyra et al, 2006) studies have examined mineral formation in super-saturated systems and have found a close spatial association between bacterial cells and a range of extracellular precipitated mineral phases. Despite the increasing number of studies to claim the importance of passive cell wall biomineralization (Lowenstam and Weiner, 1989;Châtellier et al, 2001;Ben Chekroun et al, 2004;Beazley et al, 2007;Dupraz et al, 2009), the nature of the evidence to date is equivocal. A range of studies have documented associations between bacterial cells and mineral precipitates (Konhauser, 1997(Konhauser, , 1998Arp et al, 1998;Douglas and Beveridge, 1998;Warren et al, 2001;Perez-Gonzalez et al, 2010), but a spatial association in and of itself does not prove a role of the cell wall in the precipitation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate systems are of particular interest due to the importance of P cycles and the low solubilities of many metal-phosphate phases. Reduction of Fe(III)-oxides by iron-reducing bacteria releases Fe(II) to solution and can lead to the precipitation of vivianite (Fe 3 (PO 4 ) 2 Á8H 2 O), which is a major sink for Fe and for heavy metals in fresh water sedimentary systems (Taylor and Boult, 2007); anthropogenic contamination of groundwater and soil systems can lead to precipitation (or co-precipitation) of heavy metals as oxides and phosphate phases in these systems (e.g., Kirpichtchikova et al, 2006;Manceau et al, 2007;Terzano et al, 2007); and remediation strategies such as phosphate amendments rely on precipitation reactions in bacteria-bearing systems to reduce concentrations of dissolved metals in systems, such as those contaminated with dissolved U (e.g., Beazley et al, 2007;Martinez et al, 2007;Wellman et al, 2007;Ndiba et al, 2008) or by acid mine drainage (e.g., Schultze-Lam et al, 1996). The common denominator between all of these systems is the precipitation of phosphate and other mineral phases in environments that can be rich in non-metabolizing bacterial cells and/or bacterial exudates.…”
Section: Introductionmentioning
confidence: 99%
“…To further highlight such adaptation, recent investigations of terrestrial and marine bacterial isolates belonging to the genera Aeromonas, Bacillus, Myxococcus, Pantoea, Pseudomonas, Rahnella, and Vibrio demonstrated that Cr, Pb, and U were removed from solution as phosphate minerals under both oxic and anoxic growth conditions [57,60,74,152,[154][155][156][157][158]. Our recent work further examined lead and 6 Advances in Ecology uranium precipitates produced by Rahnella sp.…”
Section: Phosphatase-mediated Biomineralizationmentioning
confidence: 85%
“…With recent studies identifying autuniteand hydroxyapatite-precipitating capabilities of Aeromonas, Bacillus, Pantoea, Pseudomonas, and Rahnella spp. in both oxic and anoxic growth conditions, the synergistic properties of these minerals (i.e., ion-exchange reactions that sequester cooccurring metals) highlight an important role in not only stabilizing U contamination but also cooccurring metals [57,60,74,157]. Furthermore, contaminated sites that are characterized by acidic to circumneutral porewater pH represent environments that can support stable mineral formation (Figures 2(a) and 2(b)), provided that carbonates are not present in significant concentrations (i.e.,P CO 2 < 10 −3.5 atm) [176,177].…”
Section: Challenges For In Situ Immobilization Of Metals and Radionucmentioning
confidence: 99%
“…This work illustrated that although uranyl phosphates are considered to be sinks of uranium and therefore strong candidates for remediation strategies (Beazley, R. et al 2007), the experimental results demonstrates their liability in the presence of bacteria.…”
Section: Discussionmentioning
confidence: 80%